The use of transversely tubularized bowel segment for segmental ureteral replacement - (:unkn) unknown (KARGER, 2003)
The aim of the present study was to evaluate the results of the use of a new technique, i.e. transversely tubularized bowel segment (TTBS) for segmental ureteral replacement in pigs. Eight pigs had segmental left ureteral replacement with the TTBS technique, via midline incision in 5 and flank incision in 3. The right ureters were left untouched and used as controls. The pigs were evaluated by excretory urography approximately 3 months after surgery and then sacrificed thereafter, harvesting the kidneys, ureters, and the bladders en bloc for macroscopic and histologic examination. Three pigs died in the early postoperative period. The remaining 5 pigs were followed for 82-112 days. Postoperative intravenous urograms revealed moderate ureterohydronephrosis in 2, mild ureteral dilation in 1, and normal upper tracts in 2. The 2 pigs with moderate ureterohydronephrosis had had midline incisions, and examination after having sacrificed these pigs revealed many intestinal adhesions to the anastomotic region. Easy catheterization of each left ureter through ileal ureteral segment and histologic examination thereafter demonstrated that all ileal ureteral segments including anastomotic sites were patent. Adjacent to the junctional area, metaplastic transitional epithelium covered atrophic villi and in some regions crypts as well. Ureteral replacement by the TTBS technique seems to be a safe and effective surgical treatment option in segmental ureteral defects in short term. However, long-term follow-up studies are needed. Copyright (C) 2003 S. Karger AG, Basel.
Keywords: pig; ileum; ureter; ureteral replacement